Objective Evaluation of the Quality of Movement in Daily Life after Stroke - van Meulen, Fokke B.; Klaassen, Bart; Held, Jeremia; Reenalda, Jasper; Buurke, Jaap H.; van Beijnum, Bert-Jan F.; Luft, Andreas; Veltink, Peter H. (Frontiers in Bioengineering and Biotechnology, 2016)
Stroke survivors are commonly left with disabilities that impair activities of daily living. The main objective of their rehabilitation program is to maximize the functional performance at home. However, the actual performance of patients in their home environment is unknown. Therefore, objective evaluation of daily-life activities of stroke survivors in their physical interaction with the environment is essential for optimal guidance of rehabilitation therapy. Monitoring daily-life movements could be very challenging, as it may result in large amounts of data, without any context. Therefore, suitable metrics are necessary to quantify relevant aspects of movement performance during daily-life. The objective of this study is to develop data processing methods, which can be used to process movement data into relevant metrics for the evaluation of intra-patient differences in quality of movements in a daily-life setting. Based on an iterative requirement process, functional and technical requirements were formulated. These were prioritized resulting in a coherent set of metrics. An activity monitor was developed to give context to captured movement data at home. Finally, the metrics will be demonstrated in two stroke participants during and after their rehabilitation phases. By using the final set of metrics, quality of movement can be evaluated in a daily-life setting. As example to demonstrate potential of presented methods, data of two stroke patients were successfully analyzed. Differences between in-clinic measurements and measurements during daily-life are observed by applying the presented metrics and visualization methods. Heel height profiles show intra-patient differences in height, distance, stride profile and variability between strides during a 10 meter walk test in the clinic and walking at home. Differences in distance and stride profile between both foot were larger at home, then in-clinic. For the upper extremities, the participant was able to reach further away from the pelvis and cover a larger area. Presented methods can be used for the objective evaluation of intra-patient differences in movement quality between in-clinic and daily-life measurements. Any observed progression or deterioration of movement quality could be used to decide on continuing, stopping or adjusting rehabilitation programs.